2022
DOI: 10.1007/s00264-022-05570-3
|View full text |Cite
|
Sign up to set email alerts
|

Alignment philosophy influences trochlea recreation in total knee arthroplasty: a comparative study using image-based robotic technology

Abstract: Purpose The ability of kinematic alignment (KA) to consistently restore trochlea anatomy in total knee arthroplasty (TKA) is unknown despite recreation of constitutional anatomy being its rationale for use. The purpose of this study was to assess if alignment choice in TKA effects the ability to restore the native trochlea groove. Methods One hundred and twenty-two consecutive patients undergoing robotic-assisted TKA using the MAKO image-based robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The consequence is an ongoing shift away from systematic mechanical alignment to more personalised alignment targets. There are by now numerous different alignment techniques and targets with standard off the shelf or customised implants [5–10, 23, 24]. The evidence about their impact is evolving, but still longer‐term comparative data is pending [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence is an ongoing shift away from systematic mechanical alignment to more personalised alignment targets. There are by now numerous different alignment techniques and targets with standard off the shelf or customised implants [5–10, 23, 24]. The evidence about their impact is evolving, but still longer‐term comparative data is pending [6].…”
Section: Discussionmentioning
confidence: 99%
“…Personalised medicine has arrived in total knee arthroplasty (TKA) [1,2]. Personalised alignment methods such as kinematic alignment, functional alignment and customised patient specific TKA are intensively debated at meetings and in the current literature [3][4][5][6][7][8][9][10][11]. Fostered by the knee phenotype concept and the findings of several large database studies, there has been considerable discussion about what we consider as normal, abnormal and pathological alignment [3,4,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…74,76 A recent CT-based radiological study reported FA results in less translation of native trochlear groove than either MA or KA, with the least alteration in groove depth of the three. 85 Furthermore, use of robotic capabilities with haptic boundary control has been demonstrated to decrease blood loss and soft-tissue trauma and to preserve the PCL footprint. 86,87…”
Section: Individualized Alignment Approaches In Tkamentioning
confidence: 99%
“…This is particularly relevant in the valgus morphotype where lateral condyle bone deficiency is encountered in at least 25% of cases [ 26 ], making the PCA an unreliable landmark. Recently it was demonstrated that using the PCA as reference for femoral component position, as is the case in KA, led to more than 20% of TKA’s having a femoral component that was more than 3° internally rotated relative to the TEA [ 24 ]. Use of the TEA as a landmark for rotation has in the past also been fraught with poor inter- and intra-observer reliability [ 68 ]; however, with the addition of CT landmarking in image-based robotic platforms, this issue is dealt with and the TEA becomes a more reproducible landmark for axial component positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Functional alignment aims to reconstruct 3D constitutional alignment within set boundaries, with a key difference being the adjustment of implant positioning based on consideration of the patient’s soft tissue envelope to achieve gaps that are considered balanced [ 22 ]. Its use for the varus morphotype has recently been detailed [ 23 ] and was shown to be both bone preserving and more consistent in achieving tibiofemoral balancing and preserving the native trochlea groove compared to KA [ 23 , 24 ]. The technique and rationale for the valgus morphotype is yet to be described.…”
Section: Introductionmentioning
confidence: 99%